Systematic Literature Review: Exploring the Relationship between Life Meaning and Emotion Regulation - Maesaroh; Herdiyan Maulana; Anna Armeini Rangkuti; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
This study aims to explore and synthesize empirical findings related to the relationship between the sense of meaning in life and the regulation of emotions through the Systematic Literature Review (SLR) approach. The background of this research is based on the importance of the meaning in life as one of the psychological resources that can strengthen the ability of individuals to manage emotions adaptively. Previous research has shown that individuals with high life meanings tend to use constructive emotion regulation strategies, such as cognitive reassessment, and less often use maladaptive strategies such as emotion suppression. The study examined nine scientific articles published between 2021 until 2025 using databases such as Scopus, PubMed, and Google Scholar. The results of the analysis show that the relationship between the two constructs is found in a variety of population contexts, such as college students, nurses, women with cancer, and individuals with postpartum depression, as well as across different cultural backgrounds. This study uses instruments such as Meaning in Life Questionnaire (MLQ), Emotion Regulation Questionnaire (ERQ), and DERS. The majority of research is quantitative with a correlational approach. In general, the results of this study show that the sense of meaning of life contributes to the strengthening of emotion regulation ability, but further research is still needed with longitudinal, experimental, and cross-cultural approaches to deepen the understanding of the relationship between causal and contextual variables.